2020
DOI: 10.1007/s00415-020-10359-8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring optokinetic after-nystagmus: potential for detecting patients with signs of visual dependence following concussion

Abstract: Concussed patients with chronic symptoms commonly report dizziness during exposure to environments with complex visual stimuli (e.g. supermarket aisles, busy crossroads). Such visual induced dizziness is well-known in patients with vestibular deficits, in whom it indicates an overreliance on visual cues in sensory integration. Considering that optokinetic after-nystagmus (OKAN) reflects the response of the central network integrating visual and vestibular self-motion signals (velocity storage network), we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Consistent with our findings, abnormality rates on either test are often < 25% with few reports of bilateral involvement ( 4 , 12 , 13 , 29 31 ). Three studies which included vertical canal vHIT showed increased detection rates with reports of abnormal function of at least one semicircular canal in 21.2–52% of patients ( 12 , 32 , 33 ). Otolith function has been mainly studied using cVEMPs with rates of saccular dysfunction ranging between 0 and 52% ( 7 , 12 , 13 , 29 , 31 , 33 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our findings, abnormality rates on either test are often < 25% with few reports of bilateral involvement ( 4 , 12 , 13 , 29 31 ). Three studies which included vertical canal vHIT showed increased detection rates with reports of abnormal function of at least one semicircular canal in 21.2–52% of patients ( 12 , 32 , 33 ). Otolith function has been mainly studied using cVEMPs with rates of saccular dysfunction ranging between 0 and 52% ( 7 , 12 , 13 , 29 , 31 , 33 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only recently have studies begun to investigate the central vestibular pathways which might be involved in post-traumatic dizziness and imbalance. Dysfunction of the brainstem/cerebellar velocity storage mechanism was demonstrated in one study ( 32 ); patients with chronic TBI and visually induced dizziness had prolonged time constants and increased slow cumulative eye position on recordings of optokinetic after nystagmus ( 32 ). In another study involving provocative visual motion stimuli, subacute TBI patients with these symptoms showed increased activation in several brain regions including area OP2 of the posterior peri-sylvian region and retro-insular cortex ( 59 ), a cortical region implicated in motion perception and integration of visual and vestibular information ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is currently believed this reflex is generated through the central processing network integrating visual, vestibular, and proprioceptive information. Symptoms related to optokinetic dysfunction could be related to the best known "visual vertigo" or "visually induced dizziness," dizziness that appears during exposure to environments with complex visual stimuli (e.g., supermarket aisles) [74].…”
Section: Visual and Ocular-motor Rehabilitationmentioning
confidence: 99%
“…Visual motion hypersensitivity represents one of the most common sequalae, affecting 70–80% of those affected by blunt head injuries 2 . The condition, also known as Visually Induced Dizziness (VID), is believed to be caused by a reweighing of sensory inputs after which the patient becomes more visually dependant 3 . VID patients have traditionally been viewed as vestibular, due largely to the nature of their symptoms being described as dizziness.…”
Section: Introductionmentioning
confidence: 99%